Forest Soil Colloids Enhance Delivery of Phosphorus Into a Diffusive Gradient in Thin Films (DGT) Sink - Konrad, Alexander; Billiy, Benjamin; Regenbogen, Philipp; Bol, Roland; Lang, Friederike; Klumpp, Erwin; Siemens, Jan (Frontiers in Forests and Global Change, 2021)
Phosphorus (P) is preferentially bound to colloids in soil. On the one hand, colloids may facilitate soil P leaching leading to a decrease of plant available P, but on the other hand they can carry P to plant roots, thus supporting the P uptake of plants. We tested the magnitude and the kinetics of P delivery by colloids into a P sink mimicking plant roots using the Diffusive Gradients in Thin-Films (DGT) technique. Colloids were extracted with water from three forest soils differing in parent material using a method based on dispersion and sedimentation. Freeze-dried colloids, the respective bulk soil and the colloid-free extraction residue were sterilized and mixed with quartz sand and silt to an equal P basis. The mixtures were wetted and the diffusive fluxes of P into the DGTs were measured under sterile, water unsaturated conditions. The colloids extracted from a P-poor sandy podzolic soil were highly enriched in iron and organic matter compared to the bulk soil and delivered more P at a higher rate into the sink compared to bulk soil and the colloid-free soil extraction residue. However, colloidal P delivery into the sink was smaller than P release and transport from the bulk soil developed on dolomite rock, and with no difference for a soil with intermediate phosphorus-stocks developed from gneiss. Our results provide evidence that both the mobility of colloids and their P binding strength control their contribution to the plant available P-pool of soils. Overall, our findings highlight the relevance of colloids for P delivery to plant roots.